United Nations Operations in Democratic Republic of the Congo: A Brief Assessment Report - Ngabu, Hypolitte Basi; Modeawi, Modeste Ndaba; Mawunu, Monizi; Ngbolua, Jean-Paul Koto-Te-Nyiwa; Koto-Te-Nyiwa Ngbolua, Jean-Paul (Abdul Media Literasi, 2024)
This study evaluates the impact of UN peacekeeping operations on the political and social stability of the Democratic Republic of the Congo (DRC). Since the 1960s, the UN has intervened through missions like ONUC, MONUC, and MONUSCO to stabilize the country. However, the DRC continues to face significant challenges, particularly in the eastern regions. The study addresses a critical gap in understanding how these interventions have affected economic development, diplomatic relations, and public perception of sovereignty consolidation. The primary aim of this study is to examine the economic consequences of UN peacekeeping operations, analyze how these missions have influenced the DRC's bi/multilateral diplomatic relations, and explore public opinion regarding the UN’s role in reinforcing national sovereignty. The study seeks to provide insights into the long-term effects of peacekeeping on the DRC’s stability. A mixed-methods approach was employed, incorporating both quantitative and qualitative data. A sample of 300 respondents, including local populations, government officials, and international actors, was surveyed. Data collection involved interviews, surveys, and document analysis. Statistical analysis was performed using SPSS to examine patterns and relationships. The findings reveal that UN peacekeeping missions have had mixed outcomes. While they have contributed to reducing direct conflict, they have not significantly boosted economic development. Diplomatic relations remain complicated due to varying perceptions of the UN’s extended presence. Public opinion is divided, with many questioning the overall effectiveness of the UN in restoring sovereignty. The study concludes that while UN interventions have been essential in mitigating conflict, their long-term economic and diplomatic impacts require further attention. Strengthening local governance and fostering economic development in collaboration with the UN are recommended. Future research should focus on the sustainability of peacekeeping missions and their potential role in driving economic growth in conflict-prone areas.